Omphalitis Leading to Retroperitoneal Abscess in a Neonate: A Case Report - Juan Pablo Orozco Hernández; Laura María Mesa-Tobón; Jaime Alberto Mesa-Franco; Luis Gabriel Vinasco- Sánchez (EL-Med-Pub, 2019)
Retroperitoneal abscess in neonates is extremely rare and can be fatal in case of late diagnosis. A 7-day-old newborn presented with irritability, fever, lethargy, periumbilical erythema, and a tender abdominal mass. The initial laboratory findings were a high c-reactive protein, and respiratory alkalosis. An emergent laparotomy was performed revealing a retroperitoneal abscess that required drainage. The only etiology identified in the patient was omphalitis.